SYNTHESIS AND CHARACTERIZATION OF SrCo2O4 IMMOBILIZED ON MODIFIED CLAY WITH ENHANCED REMOVAL OF CONGO RED FROM AQUEOUS MEDIUM - Sebbah, Ouardia; Bennabi, Lamia; Benhebal, Hadj; Kadi, Samir; Mahy, Julien G; Lambert, Stéphanie D (Journal of the Chilean Chemical Society, 2025)
Photocatalysis is an efficient and cost-effective method for removing toxic dyes from wastewater. Indeed, a large part of the research work carried out in the field of green chemistry has been devoted to the design and development of new photocatalysts with good photocatalytic activities. Incorporation of supports constitutes a strategy to improve the photocatalytic activity of photocatalysts by reducing the aggregation of nanoparticles during the photocatalytic process. Intercalated clays can be used as supports for oxide-based photocatalysts because they have high adsorption capacity. The goal of the present study consists of using SrCo2O4 nanoparticles as photocatalyst immobilized on natural Algerian clay modified by polyaniline (Clay/PANI/SrCo2O4). Spinel oxide (SrCo2O4) was synthesized through a sol–gel method. Then, polymer modified clay were ‎fabricated by in situ polymerization. The as-prepared composites were characterized by powder X-ray diffraction (XRD), Fourier transform infrared spectrophotometry (FTIR) and Scanning electron microscopy (SEM). The photocatalytic performances of the synthesized materials were evaluated by studying the photocatalytic degradation of congo red dye under UV light irradiation.